The Use of Flipchart Media and Anti-Hypertension Exercise in Preventing Hypertension among the Productive Age Group in Rawalo District Banyumas Regency - Nurhayati, Siti; Fitriyani, Novita Endang; Zahra, Ridha Aisya; Ulya, Fudiyana; Banuyunanto, Radhliy; Kaunia, Hafsa; Indraswari, Karavitana Puri; Ramadhani, Fatia Rahma (Indonesian Journal of Community Services Cel, 2025)
Background: The incidence of hypertension in Banyumas Regency in 2023 was 172,022 people. Rawalo District, specifically Sanggreman Village, ranked eighth in terms of the number of hypertension cases among the productive age group, with 105 people with hypertension.Aims: This activity aims to provide interventions for the prevention and control of hypertension in the productive age group through extension and counseling using flipchart media and anti-hypertension exercises.Methods: This intervention was implemented at a community health post (Posbindu) with 55 people with hypertension. The activity began with a questionnaire for the Pre-test, followed by socialization using flipcharts and anti-hypertension exercises, and concluded with a Post-test. This activity used a pre-experimental approach with a one-group pre-post test design. The sampling technique used accidental sampling. The Pre-test and Post-test methods were used to measure the level of knowledge and attitudes before and after the intervention.Results: The results of a bivariate analysis using the Wilcoxon test on the knowledge and attitude variables for hypertension prevention and control interventions in the productive age group yielded a p-value of 0.000 <0.05. This means that the intervention, through socialization and counseling using flipcharts and anti-hypertension exercises, was deemed successful, as knowledge and attitudes improved. There was a significant increase in the difference between the mean Pre-test and Post-test scores, namely 2.15 for the knowledge variable and 1.71 for the attitude variable. This indicates that people with hypertension were able to receive the information provided well through flipchart media. Anti-hypertension exercise is an example of a positive physical activity that can be easily performed by patients as a preventive effort. It is recommended that anti-hypertension exercise and flipcharts be used as health education media to reduce the incidence of hypertension in Sanggreman Village, Rawalo District.